STRONGkids validation: tool accuracy - Juliana Rolim Vieira Maciel; Eduardo Yoshio Nakano; Kênia Mara Baiocchi de Carvalho; Eliane Said Dutra (Jornal de Pediatria (Versão em Português), 2020)
Objective: Validate the accuracy of the Screening Tool for Risk on Nutritional status and Growth (STRONGkids) and estimate the prevalence of malnutrition and nutritional risk in hospitalized children. Methods: Cross‐sectional study of a representative sample of children admitted to ten public pediatric emergency rooms. The sample was randomly estimated in stages, including children older than 30 days and younger than 10 years of age, of both sexes, excluding syndromic children and those in whom it was impossible to directly measure anthropometry. Weight, height, and arm circumference were measured, as well as the Z‐scores of the anthropometric indices weight‐for‐age, height‐for‐age, weight‐for‐height, body mass index for age, and arm circumference for age, classified according to the reference curves of the World Health Organization. After the tool was applied, its accuracy tests were performed in comparison with the anthropometric data, with the evaluation of sensitivity, specificity, and positive and negative predictive values. Results: A total of 271 children were evaluated, 56.46% males and 41.70% younger than 2 years of age. The prevalence rates of malnutrition, nutritional risk assessed by anthropometric measurements, and nutritional risk assessed by the tool were 12.18%, 33.95%, and 78.60%, respectively. Accuracy showed sensitivity of 84.8%, specificity of 26.7%, positive predictive value of 49.8%, and negative predictive value of 67.2%, when the patients at nutritional risk were identified by anthropometry. Conclusion: Validation of the accuracy of STRONGkids was performed, showing high sensitivity, allowing the early identification of nutritional risk in similar populations. Resumo: Objetivo: Validar a acurácia do instrumento de triagem nutricional Screening Tool for Risk on Nutritional status and Growth (STRONGkids) e estimar as prevalências de desnutrição e risco nutricional em crianças hospitalizadas. Métodos: Estudo transversal, em amostra representativa de crianças admitidas em 10 prontos‐socorros infantis públicos. A amostra foi estimada aleatoriamente, por etapas, foram incluídas crianças com idade superior a 30 dias e inferior a 10 anos, de ambos os sexos, e excluídas as sindrômicas e impossibilitadas de aferição direta da antropometria. Foram aferidos peso, estatura e circunferência do braço, calculados os Z‐scores dos índices antropométricos peso para idade, estatura para idade, peso para estatura, índice de massa corporal para idade e circunferência do braço para idade, classificados de acordo com as curvas de referência da Organização Mundial da Saúde. Após a aplicação do instrumento foram realizados os testes de acurácia do instrumento em comparação a antropometria, foram avaliados sensibilidade, especificidade e valores preditivos positivo e negativo. Resultados: Foram avaliadas 271 crianças, 56,46% meninos e 41,70% menores de dois anos. As prevalências de desnutrição, risco nutricional pela antropometria e pelo instrumento foram de 12,18%, 33,95% e 78,60%, respectivamente. A acurácia mostrou 84,8% de sensibilidade, 26,7% de especificidade, 49,8% de valor preditivo positivo e 67,2%, negativo, quando identificados os pacientes em risco nutricional pela antropometria. Conclusão: A validação da acurácia do STRONGkids foi feita com verificação de alta sensibilidade, permitiu a identificação precoce de risco nutricional em populações semelhantes.